Gender dimensions, food security, and HIV and AIDS in internally displaced people’s (IDPs) camps in Uganda: Implications for HIV-Responsive policy and programming - Bukuluki, Paul; Mugumya, Firminus; Neema, Stella; Ochen, Eric Awich (International Food Policy Research Institute, 2008)
This study set out to investigate in specific terms how gender relations influence the interaction between food insecurity and HIV/AIDS in two armed conflict-affected districts, Gulu, in northern Uganda and Katakwi. The study largely embraced qualitative and ethnographic approaches of investigation supplemented by quantitative approaches. An exploratory and descriptive study design largely applying an ethnographic approach was employed. This facilitated the research team to gain a clear understanding of the local meanings and contextual issues that influence interactions between gender, food insecurity, and risky sexual behavior in situations of internal displacement. Quantitative variables were also generated from the ethnographic phase of the study.